Risk-based AML–CFT compliance in banking: A literature synthesis toward a compliance orchestration framework - Priatno, Aris; Suryatno, Panca Hadi; Hutagaol, Poltak Maruli John Liberty (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
This study examines the implementation of anti-money laundering and counter-terrorism financing (AML–CFT) compliance through the risk-based approach (RBA) in the banking sector and proposes a compliance orchestration framework to explain the interrelationship between regulatory, governance, operational, and technological dimensions of AML–CFT implementation. The study employs a systematic literature review (SLR) following PRISMA guidelines. From 243 identified articles, 31 articles satisfied the inclusion criteria and were analyzed through thematic synthesis and bibliometric mapping using VOSviewer to identify conceptual structure and thematic relationships within the literature. The findings demonstrate that RBA-based AML–CFT implementation operates as an integrated compliance orchestration system comprising six interrelated dimensions: regulatory anchoring, risk intelligence, operational controls, technology enablement, human and governance capacity, and supervisory interface. The analysis further reveals a significant shift in the AML–CFT literature from prescriptive rule-based compliance toward more adaptive, governance-oriented, and risk-intelligence-driven approaches, particularly in response to increasing financial digitalization, product complexity, and evolving customer risk profiles. This study contributes to the AML–CFT literature by developing a compliance orchestration framework that integrates regulatory interpretation, risk governance, operational controls, technological capability, and supervisory coordination within a unified analytical perspective. The framework provides a conceptual foundation for future empirical research and offers practical insights for banks and regulators in developing more adaptive, proportionate, and accountable AML–CFT compliance systems.